Bright and ultrafast electron point source made of LaB6 nanotip. Issue 9 (31st March 2023) - Bhorade, O.; Deconihout, B.; Blum, I.; Moldovan, S.; Houard, J.; Normand, A.; Jagtap, K.; More, M.; Vella, A.
Abstract : For the first time, we investigate strong-field photoelectron emission from LaB6 needles, opening the way towards new sources of ultra-short pulses of electrons. Abstract : The development of time-resolved transmission electron microscopy (TEM), ultrafast electron spectroscopy and pulsed X-ray sources relies on the realization of stable and high brightness sources of ultra-short electron bunches with a long service time. The flat photocathodes implanted in thermionic electron guns have been replaced by Schottky-type or cold-field emission sources driven by ultra-fast laser. Recently, lanthanum hexaboride (LaB6 ) nanoneedles have been reported to have high brightness and high emission stability when working in a continuous emission mode. Here, we prepare nano-field emitters from bulk LaB6 and we report on their use as ultra-fast electron sources. Using a high repetition rate laser in the infrared range, we present different field emission regimes as a function of the extraction voltage and laser intensity. The properties of the electron source (brightness, stability, energy spectrum and emission pattern) are determined for the different regimes. Our results show that LaB6 nanoneedles can be used as ultrafast and ultra-bright sources for time-resolved TEM, with better performances as compared to metallic ultra-fast field-emitters.